TINJAUAN YURIDIS PELAKSANAAN ISBAT NIKAH DI PENGADILAN AGAMA LUBUK PAKAM DALAM PERSPEKTIF HUKUM POSITIF - Asrinawati Oktavia Siregar; Randi Hadamean Batubara (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study examines the phenomenon of Isbat Nikah (legalization) in the Lubuk Pakam Religious Court. Interestingly, the Lubuk Pakam Religious Court experienced problems in implementing Isbat Nikah activities based on PMA Number 1 of 2015. After the enactment of Law / 1/1974 on Marriage, some people did not register their marriages before the Office of Religious Affairs. Not only that, there was also found in the field that lost the Marriage Certificate. This type of research is normative law, which will examine the laws and regulations regarding marriage. While the source of data in this study is positive law in Indonesia. Such as, Law / 1/1974, and KHI. It can be concluded that there are several factors for applying for Isbat Nikah at the Lubuk Pakam Religious Court, including: 1) due to loss of marriage certificate, 2) to arrange divorce, 3) to get married before the enactment of Law / 1/1974. The issue of recognition of having been married under the law can be submitted by filing an application with the Court. One of the reasons the judge decided the Isbat Nikah case at the Lubuk Pakam Religious Court was because it had permanent legal force, namely the applicant who filed the Isbat Nikah case in the Court.